The relationship between macroeconomic factors and business bankruptcy in developing countries - Siti Aishah, Ibrahim (2020)
Bankruptcy is a genuine problem worldwide, and it is considered a global evolution. Identified the factors of bankruptcy is a dire vital for taking curative and corrective measures for a better financial planning, profitability, liquidity, and solvency efficiency of the firm. Therefore, the main objective of this study is to investigate the relationship between macroeconomic factors and business bankruptcy cases for the period of 2007- 2019. Unlike previous studies, which have generally focused on one or compares between two countries, this study seeks to explore the relationship for 20 developing countries where linear regression models are applied in order to conclude on the regression function. The main finding is that macroeconomic variables of GDP, inflation, interest rate, unemployment rate, and corporate tax rate appear to be important factors influencing business failures. The result is obvious for countries with large GDP size compare to the countries with small size of GDP.